(untitled) (Scientific journal of the Fergana State University, 2023)
The systematic regulation of library activities, the enrichment of scientific and fiction literature in it and their in-depth research are the basis for the growth of the spiritual and educational sphere in society. The activity of scientific libraries, in particular, is the foundation for the development of the scientific sphere. The study explores the history and stages of development of first libraries in the Republic of Karakalpakstan. This article differs from other studies in this direction in that it highlights the role of such first libraries in the conduct of scientists’ researches.